Prinsip Dasar Mekanisme Pasar Dalam Islam - Sarjan, Muhammad; Siradjuddin, Siradjuddin; Sabbar Dahham, Sabbar Dahham (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2023)
Islam is a perfect, universal and dynamic way of life in governing all aspects of human life, including Islamic principles in governing market mechanisms. Price provisions are left to the natural market mechanism. The Islamic system refuses to set prices by the authorities, because Allah is the one who determines them. The price that is formed must be in accordance with the forces of supply and demand of the market, therefore the price of goods cannot be set by the government, the price provisions depend on the law of supply and demand. The Islamic system strongly promotes fair prices by encouraging perfect market competition. In order to fulfill a fair price, it is necessary to have morality (fair play), honesty (honesty), openness (transparency) and justice (justice) and avoid all kinds of speculation. If these values are enforced, then there is no reason to reject market prices. The Islamic economic system still provides opportunities under certain conditions to carry out price interventions by the government when market distortions occur, both caused by natural factors and the deviant behavior of market players.